When Law-And-Order Politics Fail: Media Fragmentation and Protective Factors That Limit the Politics of Fear - Lee, Murray (The British journal of criminology, 2022)
Law-and-order politics has long been a topic of scholarly work. The leveraging of fear of crime for political capital has been of particular concern. In the 2018 election in the Australian state of Victoria, crime and law-and-order became prominent political issues, particularly through racialized discourse about ‘African gangs’. That election provides a case study here. This article turns the traditional analysis of the politics of fear of crime around and considers some of the key reasons why law-and-order politics failed to gain decisive political traction in this instance. Media fragmentation and diversification continues to challenge the primacy of political primary definers in unpredictable ways. As such, electoral strategies that seek to leverage fear of crime and community insecurity need to be understood in the context of broader individual, community and social protective factors that might mitigate fear of crime.